Increasing Frequency of Parkinsonian Syndrome as a Reason for Admission to the Neurology Department of Befelatanana University Teaching Hospital, Madagascar - Rasaholiarison, Nomena Finiavana; Glorien Lemahafaka, Jemissair; Andriamasinavalona Rajaonarison , Lala; Ratsimandresy, Manambina; Larissa Rakotomanana, Jenny; Djacoba Tehindrazanarivelo, Alain (European Scientific Journal, ESJ, 2022)
The number of parkinsonian syndrome patients in Africa is increasing. This study evaluated the increasing number of parkinsonian syndrome (PS) patients admitted to a hospital in Madagascar. A comparison was carried out between parkinsonism syndrome plus (PS+) and idiopathic Parkinson’s Disease (PD) cases. Retrospectively, case records of patients with parkinsonism was reviewed between 2009 and 2018 in the Neurology Department of Befelatanana University Teaching Hospital, Antananarivo. Out of the 7343 patients seen in the unit over this period, 157 patients with PS were retained. It was found that PS frequency has increased significantly as a reason for admission since 2013. PS as a reason for admission rose from 0.64 % in 2009 to 29.30 % in 2018. The median age of diagnosis of PS was 60.75 years Â± 10.66. The mean age of disease onset was 57.95 years Â± 10.99, with a mean diagnosis delay of 3.19 years and a sex ratio of 1.275. Among those with PS, 112 (71.33%) had PD and and 45 (28.66%) had other parkinsonian syndromes. It was also found that patients with PD had a longer diagnosis delay (p = 0.039), a higher Mini-Mental Status Examination (MMSE) scores (p = 0.035), and they were more dopa-sensitive (p = 0.007) than those with other parkinsonian syndromes. In the facility in Madagascar, the number of referrals for PS and PD has increased over time and they have the same features as parkinsonian syndromes in other African countries.